Controlling drug-resistant bacteria in Arabian horses: bacteriophage cocktails for treating wound infections - Khalid, Esraa; Tartor, Yasmine H.; Ammar, Ahmed M.; Abdelaziz, Rewan; Mahmmod, Yasser; Abdelkhalek, Adel (Frontiers in Veterinary Science, 2025)
Antimicrobial resistance is a major global health issue requiring a coordinated response. This study investigated for the first time the prevalence, antimicrobial resistance phenotypes of bacteria causing infections in Arabian horses, and the potential of bacteriophage therapy for wound treatment. One hundred clinical samples from infected Arabian horses, presenting respiratory disorders, diarrhea, abortion, wound, and ocular infection, were examined using direct sample multiplex PCR and phenotypic methods. Antimicrobial susceptibility testing of the recovered isolates was performed using panels of 37 antibiotics and broth microdilution method. Bacteriophages were isolated from horse manure. A bacteriophage cocktail was used for treating infected wounds in Arabian horses. Streptococcus equi was the most predominant pathogen isolated from respiratory infections (17/29, 58.6%), followed by Klebsiella pneumoniae and Pseudomonas aeruginosa (9/29, 31.03%, each), and Escherichia coli (7/29, 24.13%). Staphylococcus aureus and Corynebacterium ovis biovar equi were the most frequently isolated bacteria from pyogenic infections. All isolated bacteria showed resistance to multiple antibiotics. Streptococcus spp. exhibited extensive drug resistance (XDR) with complete resistance to amoxicillin-clavulanic acid, amikacin, kanamycin, streptomycin, and cefotaxime. All Staphylococcus spp. displayed multidrug resistance (MDR) phenotype. Staphylococci isolates were highly resistant to fusidic acid, β-lactams, and tetracyclines. Amoxicillin-clavulanic acid, fosfomycin, and cephalosporines were ineffective against Enterobacteriaceae isolates. Ticarcillin, clavulanic acid, and colistin were ineffective against P. aeruginosa and Acinetobacter baumannii. Pan-drug-resistant (PDR) P. aeruginosa isolate was detected in the infected wound. Two lytic bacteriophages (vB_Pae_LP125 and vB_Pae_LS225) from the Podoviridea and Siphoviridea families were isolated from the horse manure. Both phages were stable across various temperatures and pH levels. In vitro tests showed significant lytic activity against a wide range of bacterial strains. The DNA genomes of all phages displayed distinctive restriction fragment length polymorphism. A bacteriophage cocktail (vB_Pae_LP125 and vB_Pae_LS225), when combined with gentamicin, improved wound healing in infected horses. There were significant differences (p < 0.05) in the wound closure % among the gentamicin group and phage cocktaoil+gentamicin groups on days 3, 5, 7, 10, and 14. This study highlights the widespread antibiotic resistance in bacteria infecting Arabian horses and posing significant challenges to equine infection management. Bacteriophage therapy shows promise as a potential treatment for wound infections.